Jeleboardco: a sustainable design initiative rooted in tropical craftsmanship and submerged hardwood recovery - Muhammad Fuad, Intan Nor Firdaus; Mat Saad, Ahmad Zaidi; Ahmad, Ahmad Khairul Azizi; Abdul Rahaman, Ashraf; Jamaludin, Nurul Nadiah (2025)
Through the creation of handcrafted skateboards from submerged tropical hardwoods, JELEBOARDCO, a sustainable design initiative based in Malaysia, skillfully combines ecological conservation, cultural heritage, and social entrepreneurship. The initiative, which was started in Perak in 2019, mostly uses timber that has been maintained underwater in floodplains, riverbeds, and dam reservoirs. These waterlogged logs, which are frequently decades old, are an appealing and environmentally friendly substitute for traditional logging since they still have exceptional structural integrity and eye-catching natural grain patterns. Through employment and skill development, the project seeks to empower rural craftspeople and turn these heritage timbers into high-end, sustainable lifestyle goods. Fundamentally, JELEBOARDCO connects customers to larger stories of biodiversity, resource recovery, and cultural identity by using product storytelling to promote environmental consciousness. Through the combination of circular material innovation and traditional craftsmanship, the project shows how design may achieve social and ecological goals. In Malaysia, JELEBOARDCO is a scalable model for eco-innovation and rural entrepreneurship that has a high chance of being replicated in other areas dealing with comparable economic and environmental issues.